Hierarchical Li4Ti5O12-TiO2 microspheres assembled from nanoflakes with exposed Li4Ti5O12 (011) and anatase TiO2 (001) facets for high-performance lithium-ion batteries. (20th December 2016) - Liu, Guangyin; Liu, Xiaodi; Wang, Lin; Ma, Jianmin; Xie, Haiquan; Ji, Xiaoguang; Guo, Jiali; Zhang, Ruixue
Graphical abstract: Highlights: LTO-TO microspheres with exposed LTO (011) and anatase (001) facets are prepared. CTAB plays a crucial role in the phase and morphology of the LTO-TO microspheres. LTO-TO microspheres have high capacity and excellent cycling stability. LTO-TO microspheres have good rate capability, especially at high current density. Abstract: Hierarchical Li4 Ti5 O12 -TiO2 microspheres are synthesized via an oil/water interface method with the assistance of cetyltrimethylammonium bromide (CTAB) and following calcination. The as-prepared Li4 Ti5 O12 -TiO2 microspheres are consisted of nanoflakes ( ca. 15 nm in thickness); moreover, Li4 Ti5 O12 and anatase TiO2 in the nanoflake building blocks are bounded by (011) and (001) facets, respectively. More especially, it is found that CTAB plays a very important role in the phase and morphology of the Li4 Ti5 O12 -TiO2 composite. When employed as the anode materials for lithium-ion batteries, the Li4 Ti5 O12 -TiO2 microspheres show initial discharge capacities of 234, 170, 151 and 140 mAh g −1 at charge/discharge rate of 1, 5, 10, and 20C, respectively; furthermore, after 100 cycles at 5C, the discharge capacity remains at 158 mAh g −1 with a capacity retention of 92.9%. The excellent electrochemical properties of the product can be ascribed to the synergistic effect of the exposed Li4 Ti5 O12 (011) and anatase TiO2 (001) facets, abundant phase interfaces, hierarchical structures, and thin flake-like building blocks.